2009
DOI: 10.1111/j.1462-2920.2009.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel and daily fluctuations in virioplankton production in coastal ecosystems

Abstract: SummaryViruses saturate the world around us, yet a basic understanding of how viral impacts on microbial host organisms vary over days to hours, which typify the replication cycles of aquatic viruses, remains elusive. Thus, diel patterns of viral production (VP) in Chesapeake Bay surface waters were examined on five sampling dates. Day-to-day variations in VP in the Chesapeake and coastal California surface waters were also investigated. Significant variations in VP were detected over 24 h cycles during four o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 59 publications
4
31
2
1
Order By: Relevance
“…During the time of increased bacterial growth, low levels of %BP-VIR were measured in A and SD. Initial levels for VPlytic and %BP-VIR were in agreement with published data for the Mediterranean Sea (Bettarel et al, 2002;Boras et al, 2009) and other coastal systems (Winget and Wommack, 2009). At T1, VPlytic was particularly low in A and SD, and, while it still fell within the published range for the oligotrophic Northwestern Mediterranean (Boras et al, 2009), it was lower than anticipated FIGURE 4 | Frequency of lytically infected cells (% FLIC, A) and lysogenic cells (% FLC, B) in the different treatments at T-1, T1, T4 and T8.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…During the time of increased bacterial growth, low levels of %BP-VIR were measured in A and SD. Initial levels for VPlytic and %BP-VIR were in agreement with published data for the Mediterranean Sea (Bettarel et al, 2002;Boras et al, 2009) and other coastal systems (Winget and Wommack, 2009). At T1, VPlytic was particularly low in A and SD, and, while it still fell within the published range for the oligotrophic Northwestern Mediterranean (Boras et al, 2009), it was lower than anticipated FIGURE 4 | Frequency of lytically infected cells (% FLIC, A) and lysogenic cells (% FLC, B) in the different treatments at T-1, T1, T4 and T8.…”
Section: Methodssupporting
confidence: 90%
“…Viruses do not all have the same latent period and the possibility that lysis did not occur during the incubation or occurred during a long time interval (e.g., between 12 and 24 h) cannot be excluded. Winget and Wommack (2009) found that maximum VLP abundance was recorded at different times between spring and winter in coastal-system incubations. Cell death or inactivation due to intense light conditions at the sampling time and area may have also contributed to low VPlytic.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Strong interactions between viruses and bacterial diversity have been previously evidenced under both natural and experimental conditions (67)(68)(69)(70). Here, the frequent occurrence of lysogenic and lytic infections in coral mucus (compared with the water column) could then be also partially responsible for the temporal variability of BCS, as shown by the Mantel test and the positive and significant correlation detected between this parameter and the abundance of mucosal viruses in F. repanda (Table 4).…”
Section: Discussionmentioning
confidence: 52%
“…Most such studies have focused on artificial experimental systems that contain only one, or at most two, virus/host pairs, with a few recent reports exploring natural environments (Chen et al, 2009;Short and Short, 2009;Winget and Wommack, 2009). However, to the best of our knowledge, no one has previously studied the dynamics of these interactions over time in complex communities at a depth comparable to that provided by this study.…”
Section: Introductionmentioning
confidence: 95%